The Influence of Use of the Problem Based Learning Model on Students' Critical Thinking Ability in History Subjects - Millah, Daiyatul; Ribawati, Eko; Fauzan, Rikza (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
This research aims to determine the effect of the problem based learning model on students' critical thinking abilities in the History subject class XI IIS at SMA Negeri 7 Tangerang Regency. The research method used in this research is quasi-experimental. The research sample consisted of 33 students each in the control and experimental classes. Sampling was carried out using nonprobability sampling techniques. The main instrument used is an essay test with 7 questions which are then analyzed using the t test. Hypothesis testing using the help of microsoft excell with a two-party t-test using the polled variance formula obtained a value of tamount= 2.672 > ttable= 1.997 with α= 0.05 so thatrejected and accepted. This shows that there is an influence of the problem based learning model on students' critical thinking abilities. problem based learning Model can be used as a reference in the History learning process to improve critical thinking skills in basic competencies 3.6 Analyze the influence of World War I and World War II on global political life (LBB and UN).